Proceedings of the 9th ACM SIGITE Conference on Information Technology Education 2008
DOI: 10.1145/1414558.1414612
|View full text |Cite
|
Sign up to set email alerts
|

Employers' perspectives on it learning outcomes

Abstract: As part of the assessment process of our BS in Information Technology (IT), we sought the perspective of IT employers on needed skills and knowledge for a career in IT. To this end, we conducted structured interviews with 10 IT employers in the Chicago area.Starting with an open-ended query, we asked for knowledge, skills or competencies that they particularly value when hiring IT graduates. We then asked for feedback on four preselected competencies. All four competencies were framed in technology-independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…To copy otherwise, to republish, to post on servers or to redistribute to lists, requires prior specific permission and/or a fee. IT careers [8]. The importance of these competencies is consistent with recent articles promoting architecture [1,9] and the need to compose systems from working components [5].…”
Section: Introductionsupporting
confidence: 72%
“…To copy otherwise, to republish, to post on servers or to redistribute to lists, requires prior specific permission and/or a fee. IT careers [8]. The importance of these competencies is consistent with recent articles promoting architecture [1,9] and the need to compose systems from working components [5].…”
Section: Introductionsupporting
confidence: 72%
“…One of the studies identified in the literature review pointed to a lack of multi-threaded programming ability [18]. Another study indicated that language independence among recent graduates was a problem [20]. The results of this research did not indicate that programming ability was often viewed as a problem.…”
Section: Comparison With Previous Researchmentioning
confidence: 66%
“…Miller, et al conducted a study where ten IT professionals in charge of hiring were interviewed about necessary competencies for applicants [20]. The interviewed professionals were asked about the importance of four preselected competencies (e.g.…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The IT program at DePaul University draws upon these elements using web development as the main vehicle for teaching them. Of the five required courses specific to web development, the core two-course sequence emphasizes the role of software architecture and interoperability, an emphasis endorsed in previous work [4,5].…”
Section: Early Emphasis On Architecturementioning
confidence: 99%